Sex in tourism exploring the light and the dark - 1972- Carr, Neil; 1983- Berdychevsky, Liza (Aspects of tourism, 2022)
is book encompasses the diversity and complexity of sex in tourism, including the light, dark and shades of grey between. It studies the affects and effects of diverse sexual encounters in tourism; romance tourism, sex tourism and exploitation in tourism, including the sexual exploitation of children in travel and tourism and sexual harassment"--